The Role of Conjunctions in Shaping Coherence in Japanese Texts - Nurhadi, Didik; Roni, Roni; Katoh, Jun (Makassar State University, 2025)
Abstract. Understanding the structure of a text or discourse has implications for the accuracy of understanding the meaning of the text correctly and comprehensively. Based on this problem, this article aims to describe the structure of the text through an in-depth description of the form and function of connecting expressions that build the coherence of the text. Research data was obtained through documentation from Japanese texts obtained from reading materials in Japanese language learning textbooks that are widely used by institutions in Indonesia. The analysis method is a document study type that conducts scientific work in content analysis to obtain linguistic features as characteristics of the structure of Japanese texts. This study obtained that the occurrence of conjunctions in building the coherence of Japanese texts is effectively composed according to the function of conjunctions. The presence of conjunction words in Japanese text is a keyword to understand the substructure of the text and make it easier for readers to know the importance of the content of the text in question.Keywords: Coherence; Japanese Text Structure; Conjunctions; Textual Cohesion; Linguistic Analysis